2020
DOI: 10.1007/s40314-020-01239-y
|View full text |Cite
|
Sign up to set email alerts
|

A study on impulsive fractional hybrid evolution equations using sequence method

Abstract: In this paper, we introduce a new concept called α-order cosine-resolvent family, by using the theory of fractional calculus, the concepts of measure of noncompactness and Hybrid fixed point theorem, we consider the existence of PC-mild solutions for a class of impulsive fractional hybrid evolution equation in a Banach space. Furthermore, we obtain some sufficient conditions for approximate controllability of our concern problem. At the end, an example is given to illustrate the feasibility of our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…By using a similar derivation to the mild solution of fractional impulsive systems in [9,38], we can transform system (3) into an equivalent integral expression…”
Section: Definition 1 ([35]mentioning
confidence: 99%
See 1 more Smart Citation
“…By using a similar derivation to the mild solution of fractional impulsive systems in [9,38], we can transform system (3) into an equivalent integral expression…”
Section: Definition 1 ([35]mentioning
confidence: 99%
“…Controllability of control systems is an important component and research direction of control theory, as well as the foundation of optimal control and optimal estimation. In recent years, the controllability of various types of fractional dynamic systems, including fractional impulsive systems [9,10], delay syetems [11], stochastic systems [12,13], neutral systems [14], nonlocal systems [15], damped systems [16], integro-differential systems [17], measure evolution systems [18], etc., has been studied extensively and deeply. For example, in [10], the authors derived some new results of the total controllability (a type of exact controllability) for a fractional control system with non-instantaneous impulse by means of Krasnoselskii's fixed-point theorem.…”
Section: Introductionmentioning
confidence: 99%
“…Impulsive fractional order system (IFrOS) has become a focus of research and several hundreds of articles are found by searching the topic of IFrOS from Web of Science. For the IFrOS, its equivalent integral equation is key in studying numerical solution [18, 19], existence of solution [20–28], oscillation behavior [29, 30], periodic motion [31], solvability [32], asymptotic behavior of solution [33], stability [34–36], integral solution [37–45], and so on. Furthermore, the impulsive fractional partial differential order system (IFrPDOS) was firstly introduced in [46] by {left leftarray(0+,0+)CD(s,t)eΥ(s,t)=F(s,t,Υ(s,t)),array(s,t)Θ,ssj(j=1,2,,J),arrayΥsj+,tΥsj,t=UjΥsj,t,arrayt[0,c],j=1,2,,J,arrayΥ(s,0)=η(s),Υ(0,t)=ξ…”
Section: Introductionmentioning
confidence: 99%